2022
DOI: 10.3389/fonc.2022.861206
|View full text |Cite
|
Sign up to set email alerts
|

131I-Caerin 1.1 and 131I-Caerin 1.9 for the treatment of non-small-cell lung cancer

Abstract: ObjectiveTo investigate the effect of the 131I-labeled high-affinity peptides Caerin 1.1 and Caerin 1.9 for the treatment of A549 human NSCLC cells.Methods① 3-[4,5-Dimethylthiazole-2-yl]-2,5-diphenyltetrazolium bromide (MTT) and plate clone formation assays were performed to confirm the in vitro anti-tumor activity of Caerin 1.1 and Caerin 1.9. ② Chloramine-T was used to label Caerin 1.1 and Caerin 1.9 with 131I, and the Cell Counting Kit 8 assay was performed to analyze the inhibitory effect of unlabeled Caer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Caerin 1.1/1.9 peptides are able to inhibit the proliferation of TC-1 [ 24 , 25 ], HeLa [ 26 ] and A549 [ 27 ] cells in vitro, and induce cell apoptosis, probably through the stimulation of the TNF-α signalling pathway [ 26 , 28 ]. Caerin 1.1/1.9 inhibited TC-1 tumour growth and modified the functions of tumour infiltrating immune cells, such as T cells, NK cells, and dendritic cells in vivo [ 23 , 29 ], and more activated CD8+ T cells and NK cells were recruited to the tumour sites [ 23 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Caerin 1.1/1.9 peptides are able to inhibit the proliferation of TC-1 [ 24 , 25 ], HeLa [ 26 ] and A549 [ 27 ] cells in vitro, and induce cell apoptosis, probably through the stimulation of the TNF-α signalling pathway [ 26 , 28 ]. Caerin 1.1/1.9 inhibited TC-1 tumour growth and modified the functions of tumour infiltrating immune cells, such as T cells, NK cells, and dendritic cells in vivo [ 23 , 29 ], and more activated CD8+ T cells and NK cells were recruited to the tumour sites [ 23 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the mixture containing caerin 1.1 and caerin 1.9 with an equal molar ratio (caerin 1.1/1.9, synthesised and simpli ed as F1/F3) can inhibit the growth of human and mouse cervical cancer cells, human thyroid cancer cells, and human breast cancer cells in vitro, and induce apoptosis in HeLa cells, probably through the TNFα signalling pathway, with an additive effect [21][22][23]. Coupling these peptides with nuclide can improve their anti-tumour e ciency [24]. Furthermore, F1/F3 can inhibit the growth of TC-1 cells in vivo and attract immune cells, such as T cells and NK cells, to the tumour tissue [25].…”
mentioning
confidence: 99%